2018
DOI: 10.1080/13691457.2018.1423547
|View full text |Cite
|
Sign up to set email alerts
|

Vital tasks and roles of frontline workers facilitating job inclusion of vulnerable youth

Abstract: Researchers and others are worried about the marginalisation of vulnerable youth who drop out of school and work. Frontline workers are key support givers for vulnerable youth, but they have been described as professionals who lack a recognised body of knowledge they can rely on. This article investigates vital frontline roles and tasks related to job inclusion of vulnerable youth. Qualitative data are drawn from 16Norwegian pilot projects aimed at developing social work approaches among vulnerable youth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Several studies highlight that the interpersonal cooperative and supporting relationships with co-workers and supervisors are important factors potentially increasing job satisfaction ( Belias and Koustelios, 2014 ; Gkolia et al, 2014 ). The relationship with users is essential for youth-care workers ( Fein, 2014 ; Frøyland, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies highlight that the interpersonal cooperative and supporting relationships with co-workers and supervisors are important factors potentially increasing job satisfaction ( Belias and Koustelios, 2014 ; Gkolia et al, 2014 ). The relationship with users is essential for youth-care workers ( Fein, 2014 ; Frøyland, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are considered the “front-line” professionals in residential child-care ( Seti, 2008 ) since they have the most direct and recurrent interaction with the children ( Fein, 2014 ). Helping users is an important source of pleasure and satisfaction in social services ( Ayele, 2017 ), in these contexts educators are often key support givers for children ( Frøyland, 2018 ) responding to their psychological, emotional and functional needs ( Zerach, 2013 ). The last theme is Personal Values.…”
Section: Discussionmentioning
confidence: 99%
“…Støtteapparatet si rolle i bruk av arbeidsplassar er også eitt av fleire temaområde i forsking om arbeidsinkludering av utsett ungdom (Egdell & McQuaid, 2016;Frøyland, 2018b), og forsking på overgangen frå skole til arbeid for utsett ungdom (Osgood, Foster, & Courtney, 2010;Xie, Sen, & Foster, 2014). Internasjonalt er fokuset på overgangen mellom skule og arbeid gjerne omtala som «Youth transition» eller «Transition Planning» (Luecking, 2009;Wehman, 2011).…”
Section: )unclassified
“…A final issue concerns the ways in which organizations deal with employer‐oriented services in attempts to promote clients' labour‐market participation. A Norwegian study showed that combining support for vulnerable groups with support for employers and their organizations might have a positive impact on the labour‐market inclusion of these groups (Frøyland, ), which may mitigate the tension mentioned above between strengthening welfare conditionality for vulnerable groups and focusing conditions of conduct on labour‐market reintegration. However, there is also the risk that employer‐oriented services decrease forms of support meeting the needs of vulnerable groups.…”
Section: Making Welfare Conditional: a Street‐level Perspectivementioning
confidence: 99%